Effects of formaldehyde on detoxification and immune responses in silver pomfret (Pampus argenteus). Issue 88 (May 2019) - Hu, Jiabao; Le, Qijun; Wang, Yajun; Yu, Na; Cao, Xiaohuan; Kuang, Siwen; Zhang, Man; Gu, Weiwei; Sun, Yibo; Yang, Yang; Xu, Shanliang; Yan, Xiaojun
Abstract: Formaldehyde can effectively control ectoparasites in silver pomfret ( Pampus argenteus ). However, there is limited information on the effects of formaldehyde treatment at a molecular level in fishes. In the present study, transcriptome profiling was conducted to investigate the effects of formaldehyde treatment (80 mg/L, bath for 1 h every day for three consecutive days) on the liver and kidney tissues of silver pomfret. A total of 617959982 clean reads were obtained and assembled into 265760 unigenes with an N50 length of 1507 bp, and the assembled unigenes were all annotated by alignment with public databases. A total of 2204 differentially expressed genes (DEGs) were detected in the liver and kidney tissues, and they included 7 detoxification- related genes and 9 immune-related genes, such as CYP450, GST, MHC I & II, and CCR . In addition, 1440 DEGs were mapped to terms in the GO database, and 1064 DEGs were mapped to the KEGG database. The expression of 4 detoxification-related genes and 6 immune-related genes in three days formaldehyde treatment were analyzed using RT-qPCR, and the antioxidant enzyme levels were also determined. The results indicate differential expression of detoxification- and immune-related genes during the three days formaldehyde treatment. Our data could provide a reference for the treatment of parasites to avoid high mortality and help in understanding the molecular activity in fishes after formaldehyde exposure. Highlights: RNA-seq was performed to investigate the responses of detoxification- and immune related genes to formaldehyde exposure. The formaldehyde treatment of parasites was reported to avoid high mortality in aquaculture. The treatment was assessed to be safe by mortality of fish, transcriptome level and antioxidant enzymes.